Religion and the Human Genome - Cole-Turner, Ronald (Journal of religion and health, 1992)
The study of human genetics, now greatly accelerated by the federal Human Genome Project, raises important religious questions about human health, two of which are explored. To the first questionwhether to terminate a pregnancy for genetic reasonsit is suggested that a pregnancy with a serious genetic defect may be considered at the same level of moral gravity as pregnancy from rape or incest, thereby permitting termination. To the second questionwhether genetic predispositions negate personal responsibilityit is argued that genes affect but do not determine personality and behavior.